Database systems a practical approach to design, implementation, and management - Connolly, Thomas M.; Begg, Carolyn E. (Pearson Education International, 2010)
This best-selling text introduces the theory behind databases in a concise yet comprehensive manner, providing database design methodology that can be used by both technical and non-technical readers.